Digital Marketing Strategy : A Study On Start-Up Delivery Service Business In Manggarai Regencies - Hersanius Kurnia Peong; Andy Iwan Iswanto; Mappiasse (JURNAL AKADEMISI VOKASI, 2024)
ABSTRACT This research investigates the implementation of digital marketing in start-up entrepot service businesses in the Greater Manggarai region, particularly focusing on the use of social media as the main marketing tool. Against the backdrop of the rapid development of information technology and the increasing popularity of the trust services business, this study aims to understand how businesses utilize digital marketing strategies to expand their market and increase their brand exposure. The research method used is a descriptive qualitative approach using data from online observations and interviews with drop-off service owners and customers. The results show that the majority of businesses use social media such as Facebook and Instagram as the main marketing tools, with the implementation of digital marketing strategies such as search engine optimization (SEO) to increase their online visibility. The implementation of digital marketing aims to increase brand awareness, customer numbers, and sales. Although competition in the market is getting tougher, innovation and effective marketing strategies are key to winning the competition. In conclusion, the implementation of digital marketing is a must in the growth strategy of a delivery service business in this digital era, allowing businesses to win the trust and preference of customers through consistent and relevant interactions on social media.